Simulação computacional e síntese de polímero molecularmente impresso para extração em fase sólida (MISPE) de ciprofloxacina em urina - Marestoni, Luiz Diego [UNESP] (2014)
The worldwide increase in the drug’s use is worrisome and causes environmental impacts mainly by the possibility of bacteria´s gene mutation. The concern with Ciprofloxacin should your application, being used only in severe cases. If bacteria develop resistance to this drug, can probably also develop resistance to other. However, developing analytical methods for drug determination in trace levels is difficult, by the low sensitivity or by the interfering molecules that are not possible to be separated by traditional techniques and which interfere in the more sensitive techniques results. Thus, the development of selective extracting phases to a particular drug has economic and social interests. Molecular Imprinted Polymers show a great alternative to this problem's solution. However, their development has many variables. The best choice for the monomer complex pre - polymerization is crucial for the formation of selective nanocavity. Thus, in this work we apply the semi-empirical quantum computer simulation to understand the interaction of Ciprofloxacin - monomer. We simulated the interaction with a list of 20 monomers more used in the literature. The simulations were performed using the HyperChem ® 8.0.5 software for molecular modeling, OPENEYE ® software package for verification and optimization and MMH with MOPAC 2009 to achieve the quantum energy calculation approach to theoretically predict the best monomer for synthesizing polymer proposed. The MIP was synthesized in bulk using acetonitrile as a solvent, Ciprofloxacin as template molecule, EDMA as cross linker, AIBN as radical initiator and the three monomers that were tested in the simulation to check it. The extraction of ciprofloxacin was performed in a Soxhlet system with a solution of ethanol and acetic acid 9:1 (v / v). The resulting polymer was homogenized and sieved. Rebinding analyzes were performed by isotherms and selectivity tests. The results of isotherms showed that